Lifestyle and behavioral interventions for urinary incontinence in frail older adults: An integrative review of recent evidence - Kristine M.C. Talley; Janie Thompson (Continence)
Background:: Frail older adults rely on conservative management to treat urinary incontinence (UI). Understanding the evidence on lifestyle and behavioral interventions for this population will inform optimal care and direct needed research. Aims:: To conduct an integrative review summarizing recent research and evidence on lifestyle and behavioral interventions for UI in frail older adults published in recent clinical practice guidelines, systematic reviews, and clinical trial registries. Materials and Methods:: We searched PubMed and professional organization websites for systematic reviews and clinical practice guidelines published since 2020. We searched the ClinicalTrials.gov and the International Clinical Trials Registry Platform registries to find clinical trials on the topic registered in the past 10 years. Results:: We found two clinical practice guidelines both from the 7th International Consultation on Incontinence, five systematic reviews, and five registered clinical trials. The systematic reviews included 53 individual trials conducted between 1981 and 2021 with 82% published before 2010. The most evidence existed for prompted voiding and individualized combination therapy that includes functional training. Discussion:: Frail older adults are rarely included in research on lifestyle and behavioral interventions for incontinence and are overlooked in clinical practice guidelines. There remains a paucity of evidence on the effectiveness of lifestyle and behavioral interventions for frail older adults with UI. We urge professionals to include considerations for frail older adults in their clinical practice guidelines, systematic reviews, and future research studies.